Clinical and Histopathological Features and Potential Pathological Mechanisms of Skin Lesions in COVID-19: Review of the Literature - Kaya, Gürkan (Dermatopathology (Basel), 2020)
In recent weeks, several reports have emerged of skin lesions with different clinical presentations in COVID-19 cases. All dermatologists should be aware of these cutaneous lesions, which may be early clinical symptoms of infection. We reviewed the literature on cutaneous manifestations in the PubMed database from December 2019 and June 2020. From the cases described as case reports or series in 57 recent articles, it appears that skin lesions (i) are highly varied, (ii) may not be related to the severity of the condition and (iii) resolve spontaneously in a few days. The frequency of these lesions in COVID-19 patients varies between 1.8% and 20.4%. The major clinical forms described were maculopapular eruptions, acral areas of erythema with vesicles or pustules (pseudochilblain), urticarial lesions, other vesicular eruptions and livedo or necrosis. The lesions were mainly localized in the trunk and extremities. The majority of patients were male, aged between 4.5 and 89 years. A minority of the patients were children presenting with acral, chilblain-like lesions, papulo-vesicular eruptions or Kawasaki disease-like pediatric inflammatory multisystem syndrome. The mean duration of the lesions was a few days, but some lasting as little as 20 min and others as long as four weeks have been reported. The mean latency time in the majority of cases was between 1 and 14 days; however, in some patients, lesions appeared 2 to 5 days before the onset of COVID-19 symptoms. The histopathological features of these lesions also vary, corresponding to the diversity of clinical manifestations. These features underline the nature of epidermal and dermal vascular lesions—and in severe cases, microvascular injury and thrombosis—associated with COVID-19, and provide important clues to their pathological mechanisms.